Kausalitas antara pertumbuhan ekonomi, pengeluaran pemerintah dan indeks pembagunan manusia Kabupaten/Kota di Provinsi Jambi - Uswatun Hasanah, Lisa; Hodijah, Siti; Safri, Muhammad (Jurnal Paradigma Ekonomika, 2022)
This study aims to: (1) To analyze the long-term and short-term relationship between economic growth, government spending and human development index in districts/cities in Jambi Province. (2) To analyze the causal relationship between economic growth, government spending and human development index in regencies/cities in Jambi Province. The data used is panel data from 11 districts/cities in Jambi Province during the period 2010-2020. Analysis of the data used is the Panel Vector Error Correction Model (PVECM) and the Granger panel causality test. The results of the study conclude that: (1) There is a positive long-term relationship between the human development index, government spending on education and health on economic growth. In the short term, there is a negative relationship between economic growth, spending on education and health on the human development index. Then there is a positive relationship between government education and health and economic growth. (2) Causality test Granger's results state that there is a two-way causality between economic growth and the human development index, then between government competition and HDI. Furthermore, there is a one-way causality (unidirectional causality) between the government contest and economic growth.